The Impact of Bank Interest (Riba) on Economic Growth and Development - Matondang, Sabrina Natasya; Alqorni, Muhammad (Medan Resource Center, 2023)
This article contains the impact of usury from a legal perspective and its interpretation as well as bank interest from a review of Islamic law and analyzes its impact on economic development, both as stated by Islamic law experts and based on hadith books. There are several differences of opinion in the consideration of establishing bank interest laws in Islam. Some scholars are of the opinion that bank interest is not permissible and is forbidden because it includes usury. On the other hand, there are also scholars who are of the opinion that bank interest is not haram unless bank interest is multiplied or the amount is not reasonable. This difference of opinion is referred to by differences in interpretation of the verses and hadiths regarding usury. The impact of bank interest or usury on economic development can hinder economic development. The research method for writing this journal uses the literature method or literature review by looking deeply at several books, articles and hadiths about bank interest. The purpose of this writing is to determine the impact of bank interest on economic development.